Pengaruh Ukuran Perusahaan terhadap Restatement Laporan Keuangan dengan Corporate Governance sebagai Variabel Moderasi - Dewi Kusuma Wardani; Roswita Rivernal Oba (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The purpose of this study is the influence of corporate finance on the restatement of reports with corporate governance as a moderating variable. This study uses the population of manufacturing companies in 2016-2020 which are listed on the IDX. Sampling is based on the non-probability sampling method with a targeted sampling technique. This research uses logistic regression analysis technique. The results of this study found that firm size had no effect on restatement of financial statements and corporate governance could not weaken the positive effect of firm size on restatement of financial statements.